GUIDING ROLE OF THE TEACHER IN HIGH SCHOOL - Morillo, Maricarla; Nuñez, Maricely (Revista Arbitrada Formación Gerencial, 2024)
Research aimed at describing teaching tasks from their guiding role in General Secondary Education. Based on the professional profile proposed by the School of Education of the University of Zulia in its curricular design, articulated with theoretical proposals from Amezcua, Pérez and Valladares (2004), Brooks and Brooks (1999) and Martínez-Salanova (2002). Descriptive and field research. A questionnaire with a Likert scale of 0.96 reliability was designed and applied. The sample, represented by the entire population, distributed as follows: fifteen (15) teachers and seventy (70) students in the 1st year of General Secondary Education. Concluding that, teachers fulfill tasks such as: personalized attention, referral of students, stimulation of students’ personal growth, among others.